Knowledge, Attitude and Practice about Hepatitis B, Hepatitis C and Human Immunodeficiency Virus among Barbers of Sylhet, Bangladesh (Medicine Today, 2020)
Introduction:This study was designed to see the knowledge, attitude and practice of barbers regarding transmission of hepatitis B, C and HIV viral infections.Materials and Methods: Barbers from Sylhet were interviewed with a predesigned questionnaire. Positive answers for blood transfusion, syringe sharing, use of contaminated shaving instruments and unsafe sex as way of transmission were taken as correct. Statistical analysis was done using SPSS 20 version.Result: Total 403 barbers, age from 14 years to 69 years (mean 27.11) were interviewed. In this group 232 (57.6%) had education illiterate to class five level. Among them 245 (60.3%) had income below 10 thousand per month. Blood transfusion could transmit HBV, HCV and HIV was known to 136 (33.7%), 129 (32.00%) and 247 (61.30%), contaminated syringe sharing could transmit HBV, HCV and HIV respectively was known to 131 (32.5%), 127 (31.50%) and 278 (69.0%) barbers, unsafe sex could transmit HBV, HCV and HIV was known to 166 (41.2%), 158(39.2%) and 317 (78.70%) barbers respectively and Contaminated shaving instruments could transmit HBV, HCV and HIV was known to 101 (25.1%), 96 (23.8%) and 156 (38.7%) barbers respectively. In this series 84 (20.84%) barbers answered correctly. This answers differed significantly within different level of education. Their knowledge of sterilization of shaving instruments was poor.Conclusion: Knowledge of our barbers regarding transmission of HBV, HCV and HIV and sterilisatioin of shaving instruments are inadequate. Institutional education and structured professional training may improve their services and decrease transmission of blood borne viral diseases.Medicine Today 2020 Vol.32(2): 117-121